THE INFLUENCE OF THE QUALITY OF HUMAN RESOURCES, COMMUNITY PARTICIPATION, AND UTILIZATION OF INFORMATION TECHNOLOGY ON VILLAGE FUND MANAGEMENT ACCOUNTABILITYIN KLATEN REGENCY - Abdullah Fathurrahman; Rifatun Maulani; Suprihati Suprihati; Hadi Samanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The research purposes were 1) determined the effect of the quality of human resources, community participation, and the use of information technology simultaneously to the accountability of village fund management in Ceper District; 2) determined the effect of the quality of human resources on the accountability of village fund management in Ceper District; 3) determined the effect of community participation on accountability of village fund management in Ceper District; and 4) determined the effect of the use of information technology on the accountability of village fund management in Ceper District. This research type is quantitative research with the primary data source. The population were all village officials in Ceper District, Klaten Regency. The sample amounted to 65 people. The research sampling used purposive sampling technique. Data collection techniques used survey techniques by distributing questionnaires. The data analysis method used Multiple Linear Regression using SPSS. The hypothesis testing method used t test, F test, and coefficient of determination (R2). Based on the results of data analysis, it can be concluded that 1) Quality of Human Resources, Community Participation, and Utilization of IT simultaneously affect the accountability of village fund management in Ceper District, Klaten Regency; 2) The quality of human resources has a positive and significant impact on the accountability of village fund management in Ceper District, Klaten Regency; 3) Community participation has a positive and significant impact on the accountability of village fund management in Ceper District, Klaten Regency; and 4) Utilization of Information Technology has a positive and significant effect on the accountability of village fund management in Ceper District, Klaten Regency.